Delegitimisation of disliked political organisations through biased language and acronyming - Chisango, Tadios; Gwandure, Calvin (National Inquiry Services Centre, 2019)
The study investigated the use of biased language and acronyming in political organisations in South Africa and Zimbabwe. The study surveyed the discourses of political parties that were posted on the internet. Thematic content analysis was used to analyse the discourses of the political parties. The results indicated that political organisations used biased language to delegitimise the opposition. The ingroup and outgroup stereotypes were evident in the discourses. Acronyms of opposition political parties were used pejoratively. The findings of this study suggest that political parties in developing democracies have a tendency of using biased language and acronyming to disparage the opposition. Biased language and acronyming of the outgroup in African politics could result in hate speech directed at individuals and political violence.